PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANIMASI MENGGUNAKAN SPARKOL VIDEOSCRIBE PADA MATA PELAJARAN FIKIH KELAS VIII MTs AL-KAUTSAR SUMBERSARI SRONO BANYUWANGI - Suhilmiati, Endhang; Faishol, Riza; Walailah, Alfu Laila (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
This study aims to develop animation-based learning media using sparkol videoscribe on fiqh subjects in MTs Al-Kautsar Sumbersari Srono Banyuwangi. This study uses Research and Development (R&D) research with reference to the Borg & Gall research model. The subject of this trial is a material expert 1 person and a media expert learning 1 person, all validation subjects are lecturers of Islamic Religious Education study program IAI Ibrahimy Genteng Banyuwangi. Individual trials involve 3 students, small group trials involve 9 students, and large group trials involve 20 students, all test subjects are grade VIII students of MTs Al-Kautsar Sumbersari Srono Banyuwangi. The method used to analyze the data is to use descriptive statistics. The result of this study is (1) The steps of developing this learning media using the modified Borg & Gall research model. Stages or steps in this research and development through 9 stages consisting of: 1. research and information collection, 2. planning, 3. initial product development, 4. expert validation test, 5. Product revision, 6. individual and small group trials, 7. product revisions, 8. Large group trials, 9. final product revisions. (2) The feasibility of animation-based learning media using sparkol videoscribe in fiqh subjects in MTs Al-Kautsar is as follows: assessments by material experts scored an average score of 8.46 or very decent, and learning media experts earned an average score of 8.25 or very decent, individual trial assessments earned an average score of 8.20 or decent, small group trial assessments scored an average score of 8.21 or decent, large group trial assessments earned an average score of 8.60 or very decent. Based on these results, animation-based learning media using sparkol videoscribe on fiqh subjects in MTs Al-Kautsar Sumbersari Srono Banyuwangi deserves to be used as a learning medium.